Essays in Empirical Studies Based on Administrative Labour Market Data - Shihan Du (Copenhagen Business School (CBS), 2019)
This PhD thesis, entitled "Essays in Empirical Studies Based on Administrative Labour Market Data", is composed of three independent chapters, a general introduction for all three chapters at the beginning, and a brief conclusion in the end. While all three chapters are independent research papers and can be read as such, each chapter applies and compares different econometric frameworks by using individual-level administrative labour market data, addressing important topics within the field of labour economics.
hdl:10398/9702
Keywords: 650